Geospatial technology with the integration of MCDA to identify potential irrigation site for agricultural land management in Wanka watershed, Northwestern Ethiopia - Endalkachew Sisay Yegizaw; Mulualem Asfaw Ejegu (Journal of Degraded and Mining Lands Management, 2021)
Irrigation improves the productivity of agriculture in any country. Irrigation is viewed as a fundamental approach to ensure food security, improve crop productivity, income of smallholder farmers, ensure food security, alleviate poverty and improve the economy of the farming community by generating additional income. As a result, the goal of this study was to identify prospective irrigated lands for agricultural land management in the Wanka watershed in northwestern Ethiopia using geospatial technology and multi-criteria decision-making analysis. Identifying sites for surface irrigation for agricultural land management is not a simple task, which needs consideration of many criteria such as slope, soil texture, soil depth, soil drainage, land use/land cover and distance from the water supply were used to determine the best possible location. Each factor was categorized into highly suitable, moderately suitable, marginally suitable and currently not suitable. The final result showed that the watershed had a high opportunity for surface irrigation. About 498 km2 of the watershed's total area is potentially suitable for surface irrigation, whereas the remaining 443 km2 is not. In the research area, there is sufficient land area accessible for surface irrigation development if those locations with highly suitable to marginally suitable areas are properly utilized.